Endovascular treatment of patients with high-risk symptomatic intracranial vertebrobasilar stenoses: Long - Term outcomes - Djurdjevic, T; Cunha, A; Schulz, U; Briley, D; Rothwell, P; Küker, W (BMJ Publishing Group, 2019)
Background and purpose: We present the long-term outcome after endovascular treatment of symptomatic intracranial posterior circulation stenoses.